Pragmatism as a teaching philosophy in the safety sciences: A higher education pedagogy perspective. (June 2021) - Klockner, K.; Shields, P.; Pillay, M.; Ames, K.
Highlights: The history of pragmatism is presented placing its early development in the Safety Science space. A model of the 4P's of Pragmatism within the education space is presented. Pragmatism as a teaching philosophy in the safety sciences reduces the theory into practice divide. Evidence for the success of student work from higher education pedagogy which embraces pragmatism is presented. Abstract: The education of safety science professionals is a key requirement to ensuring the ongoing recognition of Occupational Health and Safety (OHS) as a profession. Safety science educators, at some point in their academic career, are required to align with an appropriate teaching philosophy, however this important aspect of education pedagogy rarely receives scholarly attention in the safety sciences. Therefore, this article makes the case for philosophical pragmatism as an overarching teaching philosophy that works well within the evidence informed safety science practice model. Pragmatism is a logical and valuable teaching philosophy which centres on linking theory, research, ideas and actions to multi-disciplinary practical applications. It is embedded in the notion that both multiple stakeholder, and multiple perspectives are required to solve practical safety-oriented problems. Pragmatism links to a reflective practitioner paradigm whereby students are asked to think critically about what they do. Further, learning is influenced by self-discovery. The key theoretical underpinnings of pragmatism are presented, as well as the 4 Ps of pragmatism (Practicality, Pluralism, Participation and Provisional) as a teaching framework. The rational for embracing pragmatism as a higher educational teaching philosophy for the safety sciences is presented. Pragmatism is seen as both a path forward in reducing the theory into practice divide for safety science educators and professionals, and a teaching philosophy which enhances the safety science pedagogy educational lens.